PEMBERIAN EDUKASI ANEMIA PADA REMAJA - Atikah, Euis; Suhartati, Sri; Hermalia, Abelina (LP2M STP Mataram, 2023)
Anemia is a common health problem throughout the world, especially in developing countries. Anemia is common in the community, especially pregnant women and adolescent girls. Adolescent girls are said to be anemic when the hemoglobin level in the blood is <12 g/dl. Adolescent girls at puberty are very at risk of iron deficiency anemia. This is due to the amount of iron lost during menstruation. In addition, it is exacerbated by a lack of iron intake, where iron in adolescent girls is needed by the body to accelerate growth and development. This community service activity aims to provide education and increase student knowledge about anemia through nutritional counseling as an effort to prevent and overcome anemia, especially in adolescent girls. This counseling iscarried out offline through on Thursday, January 12, 2023 at 10.00-11.00 WIB. The targets in this nutrition counseling are students of SMK Sehati Karawang, class 9, totaling 30 people. Based on the results of the pre-test and post-test given, it canbe concluded that there was an increase in student knowledge after being given education about anemia in adolescent girls